A New Master's Degree in Global Health: Reflections on a 5-year Experience - Madhavi Dandu (Ubiquity Press, 2016)
Background: The University of California–San Francisco's (UCSF) Master of Science (MS) degree in global health sciences, a 1-year degree program started in 2008, is the first accredited master's degree in global health in the country. Objective: The aim of this study was to review the genesis and structure of the MS degree program, and describe its progress over its first 5 years. Methods: We reviewed the program's teaching methods, academic curriculum, course evaluations, and backgrounds and outcomes of the first 127 graduates. Student opinions were gathered from anonymous course evaluations. Student outcome data and graduates' perspectives were gathered through a voluntary, anonymous, online survey. We reflect on student demand, program strengths and weaknesses, and future academic directions. Findings: The program's structure arose from three learning objectives identified by the Curriculum Committee: a multidisciplinary approach to the foundations of global health, an emphasis on research design and methods, and an application of theory to international fieldwork. The resulting broad curriculum has attracted students of diverse backgrounds, which has enriched classroom discussions. Over the first 5 years, the program revised its fieldwork project criteria to allow more flexibility in design, leading to a higher rate of publication and enabling students to graduate with an academic portfolio. Students have reported that the high faculty-to-student ratio has fostered strong mentorship relationships; this is vital as 66% of graduates work in academics. Graduates have reflected that group work in the program appropriately prepared them for their work environment. The program's experience has guided its response to: pressure to focus on medical aspects of global health; students' needs for career skill-building; financial challenges; and trends toward online didactics. Conclusions: The recent surge in interest in global health careers has created demand for academic programs. UCSF has designed the MS degree program to balance breadth and depth of learning in a multidisciplinary curriculum, and combine career preparation and theoretical learning in a one-year academic degree. The challenges of balancing breadth and depth of learning in a multidisciplinary program, and combining career preparation and theoretical learning in a one-year academic degree, have informed UCSF's MS program design.